Palliative Action of Woodfordia fruticosa Leaves Containing Woodfruticosin on Biological Redox Imbalance and Anemia in CFA-Induced Arthritic Rats - Singhai, Ashish; Ahmad, Yusra; Patil, Umesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Rheumatoid Arthritis (RA) is a chronic disorder affecting musculoskeletal and autoimmune system with inflammatory characteristics. Anemia is most prevailing, among other extra-articular complications in RA. These complications are analogous to exorbitant inflammation and biological redox imbalance which ultimately affects the quality life and life expectancy of RA patients. Objectives: The study was planned to investigate the palliative action of Woodfordia fruticosa (WF) leaf extracts and isolation from active fraction, on articular/ extra-articular complications in rats with Complete Freund’s Adjuvant (CFA) induced arthritis. Materials and Methods: The action of Petroleum ether (WFP) and Ethanolic (WFE) extracts of WF was assessed in CFA induced adult Lewis rats (180-200gm) arthritic rats. In prophylactic treatment they received WF extracts 100mg/kg p.o. for 28 successive days and therapeutic treatment from the 14th day of CFA injection. Active extract was then fractionated by solvent-solvent extraction and chromatographic techniques. The isolated compound was characterized by TLC and various spectroscopic studies. Results: WFP significantly alleviated the severity of arthritis in animals than WFE in 28 days. Remarkable reduction (p < 0.001) in various complications was observed including paw volume (85.42%), loss in body weight, erythrocyte sedimentation rate, anemia, locomotor activity, and lipid peroxidation of hepatic/ synovial tissues and increment in SOD (U/mg) activities. A compound was isolated and characterized by UV, TLC, FTIR, LCMS and NMR spectroscopic techniques. Conclusion: WFP at 100mg/kg was advantageous in the superintendence of RA intricacies which was also confirmed by the histological and radiological studies. And a tannin compound Woodfruticosin was isolated.
Keywords: Rheumatoid arthritis; Chromatography; Isolation; Spectroscopy; Woodfruticosin